Schoolscapes of Inclusion: Interpreting the Meaning of Cultural Diversity in Education - Muhammad Davin Yuzaki; Sudarsri Lestari; Vina Rohmatul Ummah (Journal of Educational Management Research, 2026)
This study aims to explore the phenomenon of cultural diversity in an Islamic elementary school and to examine students’ social interactions as well as the school’s strategic role in fostering an inclusive multicultural environment. A qualitative case study design was employed involving 36 fifth-grade students from two classes. Data were collected through classroom observations, semi-structured interviews with school stakeholders, and document analysis, and were analyzed using data condensation, data display, and conclusion drawing with source triangulation to ensure credibility. The findings indicate that students and teachers demonstrated highly positive responses toward cultural diversity through openness, mutual respect, curiosity, and collaborative learning practices that strengthened intercultural understanding. These positive outcomes were reinforced by inclusive school policies, proactive leadership in promoting tolerance, and continuous teacher guidance that emphasized equality, respect, and national unity. The integration of these strategies created a harmonious learning environment where students from different cultural backgrounds interacted constructively without discrimination. The study implies that comprehensive multicultural leadership, supported by inclusive policies and culturally responsive teaching practices, can serve as an effective framework for promoting social cohesion, equitable learning opportunities, and sustainable multicultural education in diverse elementary school settings.